2020
DOI: 10.1177/1120672120902030
|View full text |Cite
|
Sign up to set email alerts
|

Combining cataract surgery with 25-gauge high-speed pars plana vitrectomy: A prospective study

Abstract: Purpose: To compare visual outcome and postoperative complications of combined 25-gauge pars plana vitrectomy and phacoemulsification with vitrectomy alone surgery in patients with epiretinal membrane and macular hole. Methods: A total of 110 eyes (73 eyes with epiretinal membrane and 37 eyes with macular hole) were enrolled in this prospective study. The eyes were divided into two groups: Group A included 55 eyes which underwent phacovitrectomy at the same time and Group B included 55 eyes which underwent vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Due to postoperative complications involving the crystalline lens, more than half of phakic patients who underwent vitrectomy for RRD repair subsequently needed cataract surgery within 1 year [5]. Thus, combined phacovitrectomy was encouraged for patients aged 50 or older due to the lower cost of surgery, reduced complications and better visual outcome [6][7][8][9]. In 10-17% of cases of RRD with macular involvement, it was impossible to measure the axial length (AL) using optic biometry (IOLMaster) because of the limitations of the machine, such as dense media opacity, poor fixation by the patients or the lack of an available machine [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to postoperative complications involving the crystalline lens, more than half of phakic patients who underwent vitrectomy for RRD repair subsequently needed cataract surgery within 1 year [5]. Thus, combined phacovitrectomy was encouraged for patients aged 50 or older due to the lower cost of surgery, reduced complications and better visual outcome [6][7][8][9]. In 10-17% of cases of RRD with macular involvement, it was impossible to measure the axial length (AL) using optic biometry (IOLMaster) because of the limitations of the machine, such as dense media opacity, poor fixation by the patients or the lack of an available machine [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients who had undergone combined surgery showed a significantly higher CME prevalence during follow-up. Conversely, other studies have found no significant difference in CME prevalence between patients undergoing combined surgery and those undergoing PPV alone [17]. Some publications have speculated that the breakdown of the blood-aqueous-barrier due to cataract surgery, together with that of the blood-retinal barrier due to vitrectomy, could induce stronger ocular inflammatory responses in RRD eyes, leading to a higher reoperation rate after combined surgery than PPV alone [18]; however, this hypothesis is not widely confirmed by the literature.…”
Section: Discussionmentioning
confidence: 93%
“…In 2021, Savastano et al also published a prospective, comparative study involving 110 eyes with ERM or macular hole undergoing either PPV alone or combined phacovitrectomy. 28 The authors concluded there were no significant differences in visual outcomes and postoperative complications between the two group. Some studies suggest that phacovitrectomy may expedite visual recovery.…”
Section: Macular Holementioning
confidence: 92%